Bilateral acquired cystic kidney associated renal cell carcinoma with sarcomatoid features - A rare entity - Mahmut Akgul, MD; Nafiseh Janaki, MD; RajMohan Paspulati, MD; Gregory T. MacLennan, MD (Elsevier, 2018)
Acquired cystic kidney disease associated renal cell carcinoma (ACKD-RCC) is known to be the most common primary renal cell malignancy in patients with end stage renal disease, particularly those who have endured long-term hemodialysis. Most such cases present at a low clinicopathologic stage and exhibit indolent biologic behavior. Conversely, the rare cases that harbor components of sarcomatoid or rhabdoid change tend to present at an advanced stage, exhibiting aggressive behavior and a propensity to prove fatal. Our case is that of a 47-year old male who developed renal failure necessitating 13 years of hemodialysis and culminating in the development of bilateral ACKD-RCC with extensive sarcomatoid differentiation.